UPAYA MEWUJUDKAN KESADARAN ATAS HAK KEKAYAAN INTELEKTUAL BAGI PELAKU UMKM DI KOTA BANJAR - Indah Siti Aprilia; Rian Achmad Perdana; Jessica Priscilla Simanungkalit; Adriel Michael Tirayo; Tiara Jayaputeri (Fakultas Hukum Universitas Tarumanagara, 2022)
Intellectual property rights are works resulting from copyright and taste are defined as property arising from human intellectual abilities which can be in the form of works in the fields of technology, science, art, and literature. This intellectual property needs to be followed up for security through a protection system for Intellectual Property Rights (IPR). Broadly speaking, IPR consists of Copyright (copyright) and Industrial Property Rights (industrial property rights) which include patents (patents), industrial designs (industrial designs), brands (trademarks), overcoming fraudulent competition practices (repression of unfair competition). , layout design of integrated circuits and trade secrets. The socialization of intellectual property carried out to the community in Banjar City is socialization in the field of Copyright and Trademarks. This socialization is carried out regarding copyright and this brand is a field that is closely found in society. The purpose of holding this socialization is to provide information to the community in Neglasari Village, Banjar District, Banjar City to be able to understand more comprehensively regarding the requirements for trademark registration, and copyright and how the submission process is. The method used is socialization and a question and answer session with the community is carried out. The result of this socialization have enriched the knowledge of people in Banjar City regarding the laws and regulations in Intellectual Property